1983
DOI: 10.1126/science.6823571
|View full text |Cite
|
Sign up to set email alerts
|

Free-Running Activity Rhythms in the Rat: Entrainment by Melatonin

Abstract: The pineal gland hormone melatonin may play a role in synchronization of rat circadian rhythms. Free-running activity rhythms of the rat were entrained by a daily melatonin injection, with entrainment occurring when the onset of activity coincided with the time of daily injections. When injections were stopped, activity rhythms became free-running again. Thus in pharmacological experiments, the time of day of melatonin administration is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
209
2
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(219 citation statements)
references
References 15 publications
4
209
2
4
Order By: Relevance
“…When 0.5 mg melatonin 424 JOURNAL OF BIOLOGICAL RHYTHMS / October 2003 was started in the phase delay region of the PRC, some individuals did not exhibit changes in phase or period during melatonin administration and continued to free run, again in agreement with the 5-mg studies (Lockley et al, 2000). In contrast to our previous findings, however, we have shown here that when 0.5 mg melatonin is initially administered in the phase delay portion of the PRC, free-running rhythms can eventually become entrained in some individuals when an appropriate circadian time for melatonin administration is reached, analogous to the first study in mammals (Redman et al, 1983). The current study confirms and extends our finding that the CT of administration of melatonin is an important factor in determining whether entrainment occurs (Lockley et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…When 0.5 mg melatonin 424 JOURNAL OF BIOLOGICAL RHYTHMS / October 2003 was started in the phase delay region of the PRC, some individuals did not exhibit changes in phase or period during melatonin administration and continued to free run, again in agreement with the 5-mg studies (Lockley et al, 2000). In contrast to our previous findings, however, we have shown here that when 0.5 mg melatonin is initially administered in the phase delay portion of the PRC, free-running rhythms can eventually become entrained in some individuals when an appropriate circadian time for melatonin administration is reached, analogous to the first study in mammals (Redman et al, 1983). The current study confirms and extends our finding that the CT of administration of melatonin is an important factor in determining whether entrainment occurs (Lockley et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…For example, why did the subjects in the present study not entrain once they reached the appropriate advance phase, as would be predicted from the PRC and animal experiments (Redman et al 1983)? A similar lack of entrainment was observed in two sighted subjects by Middleton and colleagues (1997).…”
Section: Figurementioning
confidence: 78%
“…There is increasing evidence that the timing of melatonin secretion is closely associated with the timing of sleep propensity [17] . Melatonin administration shifts circadian rhythms in both rodents [18] and humans [19] and improves sleep by shortening sleep latency and lengthening sleep duration [19] . Melatonin has been used successfully in treating insomnia [20] www.nature.com/aps Tian SW et al Acta Pharmacologica Sinica npg and various circadian rhythm disorders such as delayed sleep phase syndrome [21] and shift-work sleep disorder [22] .…”
Section: Introductionmentioning
confidence: 99%